PERBEDAAN PENINGKATAN KEMAMPUAN KOMUNIKASI DAN KONEKSI MATEMATIS SISWA MELALUI PEMBELAJARAN KONTEKSTUAL DENGAN KOOPERATIF TIPE STAD DI SMP AL-WASHLIYAH 8 MEDAN - Rosliana Harahap; Izwita Dewi; Sumarno . (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2009)
The objectives of this study are to investigate: (1) The diffrences of improving students’ mathematical communication ability in contextual learning and cooperative learning type STAD at SMP Al-Washliyah 8 Medan, (2) The diffrences of improving students’ mathematical connection ability in contextual learning and cooperative learning type STAD at SMP Al-Washliyah 8 Medan This study is an experimental research there were six classes of Grade VII, the samples were taken two classes randomly. The first class was treated by using contextual learning  and the second class was treated by using cooperative learning type STAD. The instruments which were used; Mathematical Communication ability test, and Mathematical Connection ability test. The instruments were eligible content validity and reliability about 0,81 and 0,82 to mathematical commmunication and connection ability. The Data analyzed by appling multivariate analysis (MANOVA). The results reveal that this study, generally the students were treated by contextual learning are better than the students were treated by cooperative  learning type STAD. Based on the study, the reseacher suggested (1) Contextual learning in teaching mathemaics for improving students’mathematical  communication and connection ability would become an alternative for applying innovative mathematical learning. (2)  Students’activity through contextual learning categorized as either. This study is also expected to be useful for mathematics teacher to created good atmosphere and give a chance to the sudents for presenting their idea by themselves.